(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Gross State Domestic Product (GSDP) of a state is a quantitative indicator of the economic health of a state. Various sectors contribute to the GSDP which can be divided into primary, secondary and tertiary sectors. This paper studies the trend in the growth of GSDP of Uttar Pradesh at constant prices (2011-12) from 2011 to 2020 and the contribution of various sectors to the GSDP. This study uses secondary data from the National Statistics Office. The study reveals that the contribution of the primary sector to GSDP has fallen over the years, the contribution of the secondary sector has remained stable, and the contribution of the tertiary sector has increased.